2019
DOI: 10.3389/fphys.2019.01236
|View full text |Cite
|
Sign up to set email alerts
|

Syncytiotrophoblast-Derived Extracellular Vesicles in Pathophysiology of Preeclampsia

Abstract: Preeclampsia is a common obstetric complication associated with pregnancy and it endangers lives of the mother and the infant. The histopathological changes associated with preeclampsia include systemic endothelial dysfunction, persistent inflammatory state, and coagulation and fibrinolysis dysregulations. Preeclampsia is considered to be caused by the systemic vasoconstriction of small arteries and disruption of the endothelial integrity, resulting in hypertension, proteinuria, and multiple organ dysfunction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 87 publications
1
34
0
Order By: Relevance
“…These EVs, upon binding, induce a shift in the cytokine secretion profile of the neighboring cells, causing the release of anti-inflammatory cytokines (64). On the other hand, in preeclampsia when placental ischemia and hypoxia are present, a greater number of the STB cells undergo apoptosis (68). There is subsequently an increase in secreted EVs into the maternal circulation, overwhelming the body's ability to adequately scavenge and clear them effectively (68,69).…”
Section: Syncytiotrophoblast Cells and Their Secreted Extracellular Vmentioning
confidence: 99%
See 1 more Smart Citation
“…These EVs, upon binding, induce a shift in the cytokine secretion profile of the neighboring cells, causing the release of anti-inflammatory cytokines (64). On the other hand, in preeclampsia when placental ischemia and hypoxia are present, a greater number of the STB cells undergo apoptosis (68). There is subsequently an increase in secreted EVs into the maternal circulation, overwhelming the body's ability to adequately scavenge and clear them effectively (68,69).…”
Section: Syncytiotrophoblast Cells and Their Secreted Extracellular Vmentioning
confidence: 99%
“…On the other hand, in preeclampsia when placental ischemia and hypoxia are present, a greater number of the STB cells undergo apoptosis ( 68 ). There is subsequently an increase in secreted EVs into the maternal circulation, overwhelming the body's ability to adequately scavenge and clear them effectively ( 68 , 69 ). These vesicles then act as antigenic stimuli for components of the immune system leading to unintended endothelial injury, inflammation, and hyper-coagulation ( 68 ).…”
Section: Syncytiotrophoblast Cells and Their Secreted Extracellular Vmentioning
confidence: 99%
“…In mouse models, we further showed that these pcEVs induce hypertension and proteinuria not only in pregnant mice but also in non-pregnant mice [ 21 ], demonstrating the importance of pcEVs in the pathogenesis of PE. These pcEVs can cause PE through multiple pathways [ 48 ] by (1) promoting coagulation through PS exposed on their surfaces [ 21 , 22 , 49 ], (2) expressing tissue factor to trigger extrinsic coagulation [ 49 ], and (3) activating platelets and endothelial cells to release procoagulant extracellular vesicles [ 21 ]. Together, these findings demonstrate that PE is initiated by placental factors and propagated by maternal factors in the systemic proinflammatory and hypercoagulable states, which are closely associated with oxidative stress.…”
Section: The Pe-associated Hypercoagulable Statementioning
confidence: 99%
“…PE is a pregnancy-related hypertensive disorder characterized by an insufficient trophoblast invasion into the maternal spiral arteries, deregulated proliferation and enhanced apoptosis ( 5 , 6 ). PE is also a major contributor to perinatal morbidity and mortality ( 7 ).…”
Section: Introductionmentioning
confidence: 99%